A Within-Subject Comparison of Bimodal Hearing, Bilateral Cochlear Implantation, and Bilateral Cochlear Implantation With Bilateral Hearing Preservation. Issue 8 (September 2015) - Gifford, René H.; Driscoll, Colin L. W.; Davis, Timothy J.; Fiebig, Pam; Micco, Alan; Dorman, Michael F.
<x xml:space="preserve">Abstract</x> Objective To compare speech understanding with bimodal hearing and bilateral cochlear implants (CIs). Study Design Within-subjects, repeated-measures. Methods Speech understanding was assessed in the following conditions: unilateral hearing aid (HA) in the non-implanted ear, unilateral CI, bimodal (CI + HA), and bilateral CI. In addition, three participants had bilateral hearing preservation and were also tested with bilateral CIs and bilateral HAs (BiBi). Setting Tertiary academic CI center. Patients Eight adult sequential bilateral recipients who, despite achieving incredibly high performance with the first CI, self-selected for bilateral cochlear implantation. Intervention(s) Bilateral cochlear implantation. Main Outcome Measure(s) Speech understanding for the adult minimum speech test battery as well as sentences in semidiffuse noise using the R-SPACE system. Results Bilateral CIs afforded significant individual improvement in a complex listening environment even for individuals demonstrating near perfect sentence scores with both the first CI alone as well as the bimodal condition. The 3 BiBi participants demonstrated additional significant benefit over the bilateral CI condition–presumably because of the availability of interaural time difference cues. Conclusions These data suggest that, for noisy environments, adding a second implant can significantly improve speech understanding—even for high-performing unilateral CI with bimodal hearing. In diffuse noise conditions, bilateral acoustic hearing can yield even greater benefits beyond that offered by bilateral implantation.